The Characteristics of an Ideal Country: Perspectives from Bintu Syaṭi's Exegesis: Ciri-Ciri Negara Ideal: Perspektif Tafsir Bintu Syaṭi - Novi Laila Athiyah; Aghnin Khulqi (Aqwal: Journal of Qur'an and Hadis Studies, 2024)
Background and Objectives: The concept of the ideal state in Islamic political science is often analyzed from the perspective of male mufassirs, while women's views are rarely considered. This study explores the characteristics of the ideal state according to Bintu Shafi'. The female perspective is considered to make a significant and unique contribution to understanding the concept of the ideal state in Islam. Methodology: This research utilizes a qualitative method with a literature review approach, using al-Tafsir al-Bayani li al-Quran al-Karim as the primary source and other relevant references as secondary sources. Data were collected through documentation techniques by focusing on related keywords such as state and Bintu Shaṭi', as well as relevant Qur'anic verses. The analysis was done thematically, especially on Surah Al-Balad. Main Findings: The ideal state includes three main elements: security, food security and leadership quality. The state must be able to provide security for all citizens, especially women, maintain food security, and be led by leaders who are honest, trustworthy, transparent, and intelligent like the Prophet Muhammad. This research contributes to enriching the literature on the concept of the ideal state in Islam with a more inclusive and diverse perspective, and emphasizes the importance of including women's perspectives in the study of Qur'anic interpretation and the concept of the state. Conclusion: the perspectives of women, such as Bintu Shafi', provide valuable insights into understanding the concept of the ideal state in Islam. The ideal state pays attention to security, food security, and the quality of leadership.